Myths and Misconceptions of Traumatic Brain Injuries Among High School Learners and University Students in South Africa - Moodley, Miranda (Department of Psychology, 2021)
Traumatic Brain Injury (TBI) is a major cause of disability and death around the world with an annual worldwide prevalence rate ranging from 369 per 100 000 people (James et al., 2019). TBI is specifically more concerning in adolescents and young adults as rates of injuries acquired during this period are similar to adult rates, but with more far-reaching effects, especially in low and middle-income countries (Dewan et al., 2016). TBI has significant long-term effects (e.g., cognitive, behavioural, social) on adolescents and young adults, which are compounded in low and middle income countries (LMICs) like South Africa. However, myths and misconceptions regarding TBI and associated outcomes often cloud the understanding thereof and contribute to poor help-seeking behaviours post-TBI. Poor help-seeking behaviours post-TBI can impact TBI recovery and result in even worse impairments if appropriate help is not sought. This study aimed to describe and compare myths and misconceptions about head injuries or traumatic brain injuries (HI/TBI), including concussions, for high school learners (with/without HI/TBI) and university students (with/without HI/TBI). In terms of misconceptions, students (n=393) scored significantly higher on HI/TBI and concussion knowledge, compared to learners (n=80). Regression analyses showed that adolescence (learners) vs young adulthood (students) was a significant predictor of myths and misconceptions regarding TBI/HI; F (44, 369) = 3.32, p < .001; but not for concussion knowledge and attitudes; F (44, 369) = 1.10, p =.31 and F (44, 369) = .725, p =.904. Understanding what high school learners know and how this differs from university students' knowledge about TBI will help inform interventions tailored to adolescents and young adults – which is needed as they are a vulnerable population group.